Price fluctuations of quail eggs at the farm level and their contributing factors in The Jabodetabek and East Java - Ratu Reni Budiyanti; Vony Armelia; Magfira; Akbar Satria Bahari (Jurnal Agro Veteriner, 2024)
Quail eggs offer numerous health benefits, including enhancing the immune system, supporting brain growth and development, and repairing damaged cells. Indonesia has key quail egg production centers in East Java, with the Jabodetabek area serving as the primary consumer market. This has led to price disparities between the two regions at the producer level. From October 2023 to September 2024, the average price of quail eggs at the producer level in East Java was IDR 30,738 per kg, while in the Jabodetabek area, it was IDR 32,738 per kg. The highest prices in both regions were recorded in May, with the lowest prices observed in December. In May, the price of quail eggs in Jabodetabek reached IDR 36,000 per kg, while in December, it dropped to IDR 22,000 per kg. In East Java, the price in May was IDR 34,000 per kg, and in December, it decreased to IDR 20,000 per kg. The most significant price fluctuations in Jabodetabek occurred in February, with a coefficient of variation (CV) of 0.739, while in East Java, the highest fluctuations were recorded in both November and February, with a slightly higher CV of 0.740.